On the interaction of copper with tris(hydroxymethyl)aminomethane - Colombo, M. F. [UNESP]; Austrilino, L.; Nascimento, O. R.; Castellano, E. E.; Tabak, M. (Canadian Science Publishing, 1987)
The interaction of copper with tris(hydroxymethyl)aminomethane (TRIS) has been studied by optical and esr spectroscopic techniques. In solution, three different copper complexes are obtained as a function of pH. At pH 10 the room temperature esr parameters are g0 = 2.135, A0 = 82 G and nitrogen superhyperfine structure /tN = 9.5 G, characteristic of two nitrogen ligands; at pH 6.5, go = 2.147, A0 = 65 G and at pH 5.0, g0 = 2.180, A0 = 44 G. The high pH complex was crystallized and its molecular structure determined by X-ray methods. Space group and cell dimensions are C2/c, a = 12.955(2) Å, b = 10.793(1) Å, c= 10.091(2) Å,β= 116.62(1)°, V= 1261.4(6)Å3 = 4, Dc = 1.694gcm-3, R = 0.034 for 938 reflections with I > 3σ(I). The Cu2+ ion is located on the two-fold axis and coordinated to the oxygen and nitrogen atoms of two TRIS moieties; these ligand atoms form the rectangular base of a pyramid structure in which oxygen from a water molecule acts as the fifth ligand.